Measles Virus Suppresses Cell-mediated Immunity by Interfering with the Survival and Functions of Dendritic and T Cells - Fugier-Vivier, Isabelle (The Rockefeller University Press, 1997)
Secondary infections due to a marked immunosuppression have long been recognized as a major cause of the high morbidity and mortality rate associated with acute measles. The mechanisms underlying the inhibition of cell-mediated immunity are not clearly understood but dysfunctions of monocytes as antigen-presenting cells (APC) are implicated. In this report, we demonstrate that measles virus (MV) replicates weakly in the resting dendritic cells (DC) as in lipopolysaccharide-activated monocytes, but intensively in CD40-activated DC. The interaction of MV-infected DC with T cells not only induces syncytia formation where MV undergoes massive replication, but also leads to an impairment of DC and T cell function and cell death. CD40-activated DC decrease their capacity to produce interleukin (IL) 12, and T cells are unable to proliferate in response to MV-infected DC stimulation. A massive apoptosis of both DC and T cells is observed in the MV pulsed DC–T cell cocultures. This study suggests that DC represent a major target of MV. The enhanced MV replication during DC–T cell interaction, leading to an IL-12 production decrease and the deletion of DC and T cells, may be the essential mechanism of immunosuppression induced by MV.